PROSES PEMBERSIHAN TANGKI MUATAN CRUDE PALM OIL (CPO) DI MT. AMAS NUSA - Septyan Adi Purnomo, Suherman, Yustina S Purnomo, Suherman, Sapan (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2013)
Unpreparedness tank load space will result in losses for the company. In carrying out the cleaning of cargo tanks of crude palm oil in MT. Amas Nusa there are some problems that become obstacles in the course of cleaning cargo tanks, resulting in delays the loading process.According to tank cleaning guide, where all the ships crew must know and master the implementation of tank cleaning procedures correctly, then it needs to be revisited all matters relating to tank cleaning plan that suits your cleaning tank. Role procedures, crew, and peralatanya be reviewed in connection with the execution of the cleaning tank crude oil cargo aboard.Cause of the failure of cleaning tanks also need to be studied further for evaluation and repair operations where vessels must proceed without delay the loading of cargo tank cleaning failure. Here the role of a very large crew boat crew is considering implementing.In a theoretical basis, the author describes things related to the problem of cleaning the tank and how its implementation procedure is also associated with the on board equipment used. Things that describes the process and methods contained in the thesis made research methodology.In the analysis of data and research results about the author provides an overview presentation of research objects and the process of handling failure of cargo tank cleaning in accordance with the observations and interviews with the author of the relevant parties in the field. Then the authors compare with tank cleaning procedures guide.Finally, the writer can infer the elements in the correct implementation of appropriate cleaning tank cleaning your tank will determine the success of a new cargo ship to receive and support the smooth operation of the ship. Keyword: Tank cleaning.